Carbendazim exposure induces developmental, biochemical and behavioural disturbance in zebrafish embryos - Andrade, Thayres S; Henriques, Jorge F; Almeida, Ana Rita; Machado, Ana Luísa; Koba, Olga; Giang, Pham Thai; Soares, Amadeu M V M; Domingues, Inês (Aquatic toxicology, 2016)
Carbendazim is a widely used broad spectrum benzimidazole fungicide; however, its effects to non-target aquatic organisms are poorly studied. The aim of this study was to investigate the toxic effects of carbendazim to zebrafish early life stages at several levels of biological organization, including developmental, biochemical and behavioural levels. The embryo assay was done following the OECD guideline 236 and using a concentration range between 1.1 and 1.8mg/L. Lethal and developmental endpoints such as hatching, edemas, malformations, heart beat rate, body growth and delays were assessed in a 96h exposure. A sub-teratogenic range (from 0.16 to 500μg/L) was then used to assess effects at biochemical and behavioural levels. Biochemical markers included cholinesterase (ChE), glutathione-S-transferase (GST), lactate dehydrogenase (LDH) and catalase (CAT) and were assessed at 96h. The locomotor behaviour was assessed using an automated video tracking system at 120h. Carbendazim (96h-LC50 of 1.75mg/L) elicited several developmental anomalies in zebrafish embryos with EC50 values ranging from 0.85 to 1.6mg/L. ChE, GST and LDH activities were increased at concentrations equal or above 4μg/L. The locomotor assay showed to be extremely sensitive, detecting effects in time that larvae spent swimming at concentrations of 0.16μg/L and thus, being several orders of magnitude more sensitive that developmental parameters or lethality. These are ecological relevant concentrations and highlight the potential of behavioural endpoints as early warning signs for environmental stress. Further studies should focus on understanding how the behavioural disturbances measured in these types of studies translate into fitness impairment at the adult stage.
Keywords: dánio pruhované; Animals; Benzimidazoles; katalasa; karbamáty; cholinesterasy; plavání; Catalase; chemické látky znečišťující vodu; Swimming; Water Pollutants, Chemical; Tandem Mass Spectrometry; benzimidazoly; embryo nesavčí; vysokoúčinná kapalinová chromatografie; chování zvířat; glutathiontransferasa; Cholinesterases; Locomotion; Glutathione Transferase; Zebrafish; lokomoce; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Carbamates; Fungicides, Industrial; Behavior, Animal; Embryo, Nonmammalian; Larva; zvířata; průmyslové fungicidy; larva